The Impacts of Implementing the Information Technology to Improve the Financial Accounting Performance of PLCS - Alqudhayeb, Nael Jaafar Ali; Sabti, Yousif Mousa; Mahmood, Aseel Hadi; Hadi, Asia Hasan; Neama, Abdullah Abdulmalike (South Asian Journal of Social Sciences and Humanities, 2024)
The goal of this study is to focus the effect of information technology on the financial  accounting performance of Asian public listed companies. This study used secondary data for  120 companies from 2020 to 2023. The study also used OLS to test regression by using the  Stata program. The study found that there is a positive and important link among information  technologies on financial accounting performance. Information technology has become a focus  of interest for all financial and economic organizations because of its effect on their public and  private performance in overall and financial performance in specific. Its influence also  comprises several elements of accounting and financial performance. The study extended a set  of findings, the significant of which is the presence of a significant impact of information  technology on financial accounting performance indicators.
Keywords: Information technology; financial accounting performance; PLCs